Ramadan Of Erkin A’zam - Ko‘charova Dildora Karim qizi; Ubaydullayeva Jamila Khurramovna (Genius Publishing Group, 2022)
The article analyzes the story of Erkin A’zam “The jaydari apple of Anoi " and tries to reveal the symbolic aspects in it.
Keywords: Anoi; Ramadan; chantrimore; kalmakatore